Assessing Legal Provisions and Policies for Improving Decent Work Conditions in Nepal (The Batuk, 2023)
The purpose of this paper is to assess the legal provisions and policies for promoting decent work conditions in Nepal. It follows an integrative review of different legal documents including laws, policies, and provisions related to decent work in the Nepalese context. The evidence shows that laws and policies enacted by the government form the legislative foundation for the labor markets and decent work conditions in Nepal. Mainly, the Constitution of Nepal, 2015; Labor Act, 2017; Trade Union Act, 1992; Child Labor Act, 2000; and Sexual Harassment at the workplace (Elimination) Act, 2015 have paved the foundation for decent work in Nepal. Furthermore, Industrial Policy, 2010; Social security Fund, 2016; Youth and Small Entrepreneurs Self-Employment Fund; Agriculture Development Strategy, 2015; National Employment Policy, 2015; Foreign Employment Policy, 2012; Sustainable Development Goals, 2017; and Decent Work Country Programme for Nepal (2018-2022) have also presented the guidelines for enhancing the supportive work environment. It is found that the role of government in the transformation of business sectors and enhancement of decent work conditions is imperative, ensuring its freedom of choice, particularly in matters relating to employment relations in countries like Nepal. The findings of this paper can offer guidance for future studies on decent work and can be a milestone for open discussion on numerous legislative norms and regulations on the issue.